Analisis Tafsir Al-Quran Surah An-Nisa Ayat 171 dalam Mencegah Radikalisme melalui Medsos Studi pada Channel Youtube Ustadz Adi Hidayat - Sari, Nurlia; Monang, Sori (Universitas Syiah Kuala, 2025)
Religious radicalism is a serious challenge faced by Indonesian society, especially in the digital era when social media has become a massive and rapid means for the spread of extremist ideologies. One of the main factors contributing to the spread of radicalism is a narrow and literal understanding of religion, often neglecting historical and social contexts. This study aims to analyze the interpretation of Surah An-Nisa verse 171 as an effort to prevent radicalism through social media, focusing on Ustadz Adi Hidayats YouTube channel. This research employs a qualitative method with a case study approach, where primary data is obtained from Ustadz Adi Hidayats YouTube content discussing Surah An-Nisa verse 171 and radicalism issues, supported by secondary data from classical and contemporary tafsir literature and previous studies. The results show that Ustadz Adi Hidayat emphasizes the importance of wasathiyah (moderation) in religious practice, rejects ghuluw (excessiveness), and encourages Muslims to understand religious teachings contextually and rationally. Through systematic and interactive delivery on social media, his dawah effectively builds moderate religious literacy and prevents the spread of radical ideologies, especially among the younger generation. This study recommends strengthening moderate tafsir literacy in digital spaces as a preventive strategy against religious radicalism.